2020
DOI: 10.1038/s41422-020-00441-1
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: molecular mechanisms and health implications

Abstract: Cell death can be executed through different subroutines. Since the description of ferroptosis as an iron-dependent form of non-apoptotic cell death in 2012, there has been mounting interest in the process and function of ferroptosis. Ferroptosis can occur through two major pathways, the extrinsic or transporter-dependent pathway and the intrinsic or enzyme-regulated pathway. Ferroptosis is caused by a redox imbalance between the production of oxidants and antioxidants, which is driven by the abnormal expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
1,311
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 1,951 publications
(1,548 citation statements)
references
References 211 publications
17
1,311
1
2
Order By: Relevance
“…Ferroptosis is implicated in a variety of human diseases, such as myocardial infarction, atherosclerosis, kidney diseases, liver diseases, and neuronal diseases, as well summarized in recent review articles [22,[97][98][99][100]. Numerous ferroptosis inhibitors, including ferrostatin-1, liproxstatin-1, vitamin E analogs, and iron chelators, have been shown to effectively ameliorate disease symptoms in mouse models of each disease [22,[97][98][99]. In this review, we discussed the underlying mechanism of lipid peroxidation in ferroptosis and the various lipid metabolic pathways that control lipid peroxidation and ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroptosis is implicated in a variety of human diseases, such as myocardial infarction, atherosclerosis, kidney diseases, liver diseases, and neuronal diseases, as well summarized in recent review articles [22,[97][98][99][100]. Numerous ferroptosis inhibitors, including ferrostatin-1, liproxstatin-1, vitamin E analogs, and iron chelators, have been shown to effectively ameliorate disease symptoms in mouse models of each disease [22,[97][98][99]. In this review, we discussed the underlying mechanism of lipid peroxidation in ferroptosis and the various lipid metabolic pathways that control lipid peroxidation and ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…The conditional depletion of Gpx4 in certain tissues (e.g., kidney) triggers lipid peroxidation-dependent ferroptotic injury in mice 11 . The modulation of ferroptosis may have therapeutic potential in iron overload-associated diseases, including cancer and neurological disorders 12,13 . Although the pharmacological induction of ferroptosis is becoming a potential anticancer strategy 14,15 , the functional relevance of ferroptotic damage in oncogenic progression is poorly understood.…”
mentioning
confidence: 99%
“…Ferroptosis is a type of non-apoptotic cell death driven by excessive iron accumulation, unrestricted lipid peroxidation, and final plasma membrane damage. 5 The solute carrier family 7 member 11 (SLC7A11)-glutathione-glutathione peroxidase 4 (GPX4) axis plays a central role in blocking lipid peroxidation, whereas the endosomal sorting complex required for transport-III (ESCRT-III) machinery limits plasma membrane damage during ferroptosis. 6 More recently, accumulating evidence suggested that the biochemical machinery that induces or suppresses ferroptosis is altered in cancer cells due to the activation of oncogenes and the inactivation of tumor suppressor genes.…”
mentioning
confidence: 99%
“… 6 More recently, accumulating evidence suggested that the biochemical machinery that induces or suppresses ferroptosis is altered in cancer cells due to the activation of oncogenes and the inactivation of tumor suppressor genes. 7 The ferroptotic pathway harbors therapeutic targets for sterile inflammation and infection 5 and pharmacological induction of ferroptosis by specific agents (such as erastin [a SLC7A11 inhibitor] and RSL3 [a GPX4 inhibitor]) may selectively eliminate cancer cells carrying mutant RAS oncogene. 8 Nevertheless, in spite of the wealth of information on ferroptosis, it has remained obscure whether ferroptosis might be immunogenic.…”
mentioning
confidence: 99%